Fuel Poverty and the 2022 Energy Crisis. (30th November 2022) - Simshauser, Paul
Abstract: The Ukraine war has increased coal and gas prices during 2022. Consequently, spot prices in Australia's National Electricity Market rose from 75 to 225/MWh, year‐on‐year. Households are shielded from spot prices, but as energy retailer hedge contracts mature, they are replaced by higher cost contracts, and end‐use retail tariffs will then rise. In this article, fuel poverty levels in Queensland are analysed. Model results forecast that fuel poverty rises from 6.8 per cent to 10.5 per cent of households. However, changes to energy concessions policy in 2016‒2017 materially enhanced horizontal and vertical efficiency, with successful targeting rising from 51 per cent to 69 per cent of vulnerable households.